Analysis of Electronic Medical Record Implementation Based on HOT- FIT Factors at Ngebel Health Center, Ponorogo Regency - Aulia Kartika Windaning Tyas; Ani Rosita (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2025)
The implementation of Electronic Medical Records (EMR) is a requirement in the digital transformation of healthcare services in accordance with the Indonesian Ministry of Health Regulation No. 24 of 2022. However, EMR implementation still faces several obstacles in healthcare facilities, including at the Ngebel Public Health Center in Ponorogo Regency. This study aims to analyze the implementation of EMR based on the HOT-FIT framework, which includes four components: Human resources (Human), Organization, Technology, and Net Benefits.This research uses a qualitative descriptive approach with analysis based on the HOT-FIT framework. Data collection techniques include observation, interviews, and documentation. The subjects of this study were seven EMR users.The results show that the EMR has been implemented at the Ngebel Public Health Center since April 2023. The implementation process has been fairly good, however, challenges remain, such as internet connectivity issues and limitations in system features.This study recommends improving internet infrastructure to optimize the benefits of health services, as well as adding a digital signature (TTE) feature to the EMR system at the Ngebel Public Health Center.